Legg Calve Perthes Seen in a Tabby Cat (A Legg Calve Perthes Case in a Cat) - Yasar, TÖ; Perk, C (Journal of the Hellenic Veterinary Medical Society, 2025)
The disease was first described in humans in 1910 by three researchers, Legg, Calve and Perthes. It has been named as a hip disorder of unknown etiology that occurs in childhood. In the following years, it was determined that the disease was caused by avascular necrosis caused by the obstruction of the blood flow feeding the growing femoral head. In animals, the disease is seen as a developmental abnormality that mostly affects small breed dogs. It was first diagnosed by Tuff in 1935 in a Cairn terrier dog. This disease is much less common in cats than in dogs. A healthy cat's hip joint has a ball-and-socket shape. While the femoral head forms the "ball" part, the "socket" part consists of the depression called acetebulum in the pelvis. Ligaments and cartilages hold this structure properly and enable smooth joint movement. If the blood circulation feeding the joint is blocked, the femoral head is damaged and begins to break down. Ischemia occurs in the region, leading to the death of surrounding tissues and cartilage. The joint cannot function properly due to the malformed shape of the femoral head, which causes Legg-Calve-Perthes Disease (LCPH). The deformed joint becomes inflamed and arthritis develops. In such a case, the patient experiences severe pain. As the process progresses, the situation gradually worsens and the joint becomes unable to bear weight. The treatment protocol for the disease is still not fully finalized. However, the common goal is to correct the deformation in the hip joint and prevent degenerative joint inflammation. In this study, the rare case of Legg Calve Perthes in cats was observed unilaterally in a 1-year-old, castrated male, tabby cat. The problematic right caput femoris was removed operatively using the excisional arthroplasty technique. In the postoperative follow-up of the patient, it was observed that the right leg lameness had disappeared and all joint movements were performed without any problems. This situation was also revealed by radiological controls.